EVALUACION DE DESEMPEÑO DEL PERSONAL ADMINISTRATIVO DEL INSTITUTO ECUATORIANO DE SEGURIDAD SOCIAL( IESS) DE BABAHOYO, DURANTE EL AÑO 2007 - JOSE GABRIEL BURBANO GAIBOR (2009)
PERFORMANCE EVALUATION OF THE ADMINISTRATIVE STAFF OF THE ECUADORIAN INSTITUTE OF SOCIAL SECURITY (IESS) OF BABAHOYO, DURING THE YEAR 2007.